2010
DOI: 10.1080/02643294.2010.509340
|View full text |Cite
|
Sign up to set email alerts
|

Grammatical category dissociation in multilingual aphasia

Abstract: Word retrieval deficits for specific grammatical categories, such as verbs versus nouns, occur as a consequence of brain damage. Such deficits are informative about the nature of lexical organization in the human brain. This study examined retrieval of grammatical categories across three languages in a trilingual person with aphasia who spoke Arabic, French, and English. In order to delineate the nature of word production difficulty, comprehension was tested, and a variety of concomitant lexical-semantic varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 87 publications
1
16
0
Order By: Relevance
“…We then compared the agrammatic performance on these variables between Swahili and English. If the underlying disorder is the same in both languages, which is likely because we compared within individuals (Fabbro, 2001;Faroqi-Shah & Waked, 2010), it was expected that the reduction in utterance length and the delay in speech rate, as well as the degree in which nouns and verbs are produced would be similar in both languages. Also, we expected the agrammatic speakers to produce more ungrammatical sentences and fewer embedded sentences than non-brain-damaged control speakers in both languages.…”
Section: The Research Questions and Expectationsmentioning
confidence: 98%
See 1 more Smart Citation
“…We then compared the agrammatic performance on these variables between Swahili and English. If the underlying disorder is the same in both languages, which is likely because we compared within individuals (Fabbro, 2001;Faroqi-Shah & Waked, 2010), it was expected that the reduction in utterance length and the delay in speech rate, as well as the degree in which nouns and verbs are produced would be similar in both languages. Also, we expected the agrammatic speakers to produce more ungrammatical sentences and fewer embedded sentences than non-brain-damaged control speakers in both languages.…”
Section: The Research Questions and Expectationsmentioning
confidence: 98%
“…Presently, most work on bilingualism and multilingualism suggests that more than half the world population is bilingual or multilingual, and that the vast majority of bilingual aphasic individuals suffer from the same type of aphasia in all their languages mastered pre-morbidly (for example, Charlton, 1964;De Diego-Balaguer, Costa, Sebastián-Gallés, Juncadella, & Caramazza, 2004;Fabbro, 2001;Faroqi-Shah & Waked, 2010;Knoph, 2011). The most relevant issue in bilingual aphasia concerns differences in the pattern of recovery across the languages mastered by the bilingual speakers (see Fabbro, 2001;Paradis, 2001).…”
Section: Bilingual Aphasiamentioning
confidence: 99%
“…The authors proposed that interlanguage lexical intrusions observed among multilingual speakers with aphasia could be related to the degree of language similarity (e.g., shared vocabulary) and premorbid pattern of language use in addition to other factors such as the age and manner of language acquisition. Faroqi-Shah and Waked [11] also reported a trilingual speaker with aphasia, NK, who spoke Arabic (L1), French (L2), and English (L3). They reported dissociations between nouns and verbs in which NK demonstrated a pervasive verb production deficit irrespective of the task (confrontation naming and narrative speech) or language of elicitation.…”
Section: Introductionmentioning
confidence: 99%
“…A group of studies investigated grammatical category deficits in cross-linguistic contexts and incorporated language models into the analysis (Faroqi-Shah & Waked, 2010; Kambanaros & vanSteenbrugg, 2006; Kambanaros, 2009; Hernàndez et al, 2008a; Poncelat, Majerus, Raman, Warginaire, & Weekes, 2007; Kambanaros, Messinis & Anyfantis, 2012). A study by Weekes and Raman (2008) evaluated the effects of language type and status in one patient with deep dysphasia while discussing various models of language processing.…”
Section: Introductionmentioning
confidence: 99%